PENGARUH TANAMAN PENUTUP TANAH DAN BERBAGAI UMUR TANAMAN SAWIT TERHADAP KESUBURAN TANAH ULTISOL DI KABUPATEN DHARMASRAYA - Syafrimen Yasin; Irwan Darfis; Ade Candra (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2006)
This research was aimed to evaluate fertility level of soils under different oil palm ages and the management system. This was needed to determine when oil palm and the cover crops could give the best performance in protecting soil fertility level. Lan use types studied were divided into six groups. Those were A = palm oil plantation having cover crops at 3 years old, B = palm oil plantation having cover crops at 6 years old, C = palm oil plantation without having cover crops at 6 years old, D = palm oil plantation having cover crops at 8 years old, E = palm oil plantation without having cover crops at 8 years old, F = forest ecosystem. The result showed that based on the soil bulk volume (BV) and the soil organic matter content, deforestration for oil palm plantation did not significantly decrease soil fertility status. Soil fertility level under palm oil plantation having cover crops was better than that under palm oil plantation having no cover crops. The highest soil fertility level among the land use tested was found under palm oil plantation having cover crops at six ears old. This was proved by OC content (2.21%), N, P, K content (0.12 %, 23.92 ppm dan 0.325 me/100 g, respectively) which were comparable those of forest land use. Forest had OC = 2.31 %, N = 0.11 %, P = 17.86 ppm, and K = dan 0,33 me/100 g. While, on the other hand, the bulk volume was 1.01 g/cm3 which was lower than that under other oil palm plantation. Key Words: Tanaman Penutup Tanah, Kesuburan Tanah, Kelapa Sawit